INTERPRETATION OF SYMBOLS IN THE WORKS OF ULUGBEK HAMDAMOV - Sаrsеnbаеvа Zoyа Jаngаbаy kizi (Western European Studies, 2024)
Thе аrtiсlе dеаls with thе аnаlysis of the current level of studies in literary works within Uzbekistan, focusing on the academic and intellectual engagement with national and global literary traditions. Uzbek literary studies have evolved considerably since the country gained independence, fostering a renewed interest in both classical and modern literature. The article mainly describes the analysis of the works of Ulugbek Hamdam who also began his creative journey with short stories, and after gaining experience, he turned to novellas and novels. “While novellas and novels have brought the author considerable fame, he remains committed to the narrative form that introduced him to prose”.
Keywords: Ulugbek Hamdamov; analysis; works